2018
DOI: 10.1155/2018/6137454
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Chemotherapy-Refractory “THRLBCL like Transformation of NLPHL” Successfully Treated with Lenalidomide

Abstract: Nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) is a subtype of nonclassical Hodgkin lymphoma (HL). It resembles non-Hodgkin lymphoma (NHL), by expressing classic B cell markers such as CD20 and CD79a however lacks definitive HL markers (such as CD15 and CD30). T cell histiocyte-rich large B cell lymphoma (THRLBCL), on the other hand, is a distinct entity classified under NHL and considered a variant of diffuse large B cell lymphoma (DLBCL). NLPHL can look morphologically and immunologically similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…THRLBCL is distinguished by < 10% malignant B cells with a rich background of reactive T lymphocytes and histiocytes [4]. While it may appear morphologically similar to nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL), THRLBCL has a much more aggressive course and worse overall prognosis [14][15][16]. It typically affects middle-aged men (median age of 40 years) who often present with advancedstage disease, frequently involving the spleen, liver, and bone marrow [4,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THRLBCL is distinguished by < 10% malignant B cells with a rich background of reactive T lymphocytes and histiocytes [4]. While it may appear morphologically similar to nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL), THRLBCL has a much more aggressive course and worse overall prognosis [14][15][16]. It typically affects middle-aged men (median age of 40 years) who often present with advancedstage disease, frequently involving the spleen, liver, and bone marrow [4,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…THRLBCL is a rare, aggressive subtype of DLBCL that shares similar treatment options as DLBCL. R-CHOP is one of the mainstay systemic antineoplastic therapies for DLBCL and has been shown to have comparable outcomes in THRLBCL [4,14,15,[20][21][22][23]. Despite its efficacy, there are documented concerns with its toxicity and adverse effect profile limiting the ability of older patients (over 60 years of age) to complete therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Siricilla et al have reported a case of chemotherapy refractory THRLBCL like transformation of NLPHL which was then successfully treated with lenalidomide. 13 Surgical debulking followed by adjuvant chemotherapy (R-CHOP) is the mainstay for localized and non-metastatic gastrointestinal disease. El Weshi et al, has reported a 5-year overall survival rate of 46% with aggressive course and poor outcome.…”
Section: Discussionmentioning
confidence: 99%